Virtual reference librarians (Chatbots). Issue 4 (5th June 2017) - Vincze, Joseph
Abstract : Purpose: This paper aims to explore integrating chatbot applications into libraries to improve reference services. Design/methodology/approach: This paper explores the benefits of using chatbots as virtual reference librarians. Emma the Mentor Public Library's Catbot is used as a case study. Findings: Chatbots cannot replicate the complexity of human interaction (both knowledge and emotional), but these can provide a cost-effective way to answer the majority of routine reference questions and direct users to the appropriate service. Originality/value: Readers will increase their awareness of how chatbots can streamline the work of the reference department by answering the majority of routine reference questions and freeing library staff to focus on more demanding research and tasks uniquely suited to humans.